Oil﻿ foils corrosion in high-capacity batteries. (15th November 2018) - Unknown
Swapping out the electrolyte promises to extend the lifespan of aluminium–air batteries. Swapping out the electrolyte promises to extend the lifespan of aluminium–air batteries.